Draft Fifth Five Year Plan 1974-79 Vol. I April 1972 Andhra Pradesh - Planning Commission (Planning Commission, 1973)
Arunachal Pradesh is a thinly populated region, the northern and eastern boundaries touching China and Burma respectively. The area is approximately 83,578 Sq Km with a population of 4.675 lakhs living in 2973 villages. There are over 100 tribes with distinct culture, varied customs, and different languages and at different stages of development. There has been an increase of about 38.9% in population during the last decade. At this rate the population is likely to reach 6 lakhs at the end of the Fifth Plan. For an area as large as Arunachal, the population Might appear small but due to the rugged topography of the land even this population will find difficulty in sustenance.
Arunachal Pradesh Draft Fifth Five Year Plan
Keywords: Draft fifth five year plan for Arunachal Pradesh; Fisheries; Animal Husbandry; and Veterinary; Forests; Rural Engineering; Co-Operative and C.D.; Co-Operative; Community Development; Transport and Communication; Roads and Air strip; State Transport; Industries and Mining; Industries; Craftsmen training and Labour; Cultural Development; Social services